Circular Economy engineering through a systematic analysis fromopen science - Paredes Cotohuanza, Denisse Milagros (2024)
The objective of the study was to describe circular economic engineering by means of a systematic analysis from open science. The study was conducted in October 2023. Using the ScienceDirect database, the following search equationwith Boolean signs was entered: “circular economy model” AND “technological innovation” AND “development”. Theyears 2021, 2022 and 2023 were filtered. The selected articles corresponded to the type of review with open access. The information was analyzed using the PRISMA methodology.Thirty-two articles were identified and four were finally analyzed, corresponding to 2022 and 2023. The CE based on technological innovation considers, a traceability thatstarts with a management thinking of eco-efficient processes through sanitation and use of treated resources, distribution of marked use, consumption and optimal deposit and recycling. After 2018 none of the four articles showed matching referential citations. It is concluded, that CE is described from a variety of analyses that enable efficient and sustainable use of resources.